HISTORY OF THE SCHOOL SUBJECTS: FOUR HISTORIOGRAPHICAL APPROACHES - Juarez José Tuchinski dos Anjos (Editora da Universidade de Santa Cruz do Sul, 2013)
The present article aims at presenting a discussion on some historiographical approaches in the field of History of School Subjects, as deployed by the readings that were object of discussion in seminar conducted in the area of History and Historiography of Education, in the Post-graduation Program in Education of the Federal University of Paraná, during the first half of 2009. We investigate the approaches practiced by the Anglo-Saxon, French, Spanish and Latin American historiography, seeking to understand how each one of them, in their particular manners and from their own questions, contribute to the production of knowledge on the historicity of the school subjects.